1986
DOI: 10.2190/3lfx-9rrf-67t8-uvk9
|View full text |Cite
|
Sign up to set email alerts
|

Some Difficulties of Learning to Program

Abstract: This article is a brief introduction to some of the issues that teachers of programming may find helpful. It starts by presenting a fairly idiosyncratic view of teaching programming which makes use of mechanistic analogies and points out some of the pitfalls. The article goes on to examine certain errors based on the misapplication of analogies as well as certain interaction errors. The main emphasis is on the notional machine both at the general level of understanding (and misunderstanding) the relationship o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
228
0
24

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 487 publications
(257 citation statements)
references
References 7 publications
5
228
0
24
Order By: Relevance
“…Children find it difficult to understand the syntax and semantics of programming (Spohrer & Soloway, 1986;Perkins, 1988). They also find it challenging to effectively control the flow of a program using loops and conditionals (du Boulay, 1989). Researchers have also found that alleviating syntax problems helps students focus on the semantic ones (Hohmann, 1992;Soloway, 1993;Anderson, 1989;Mannila, Peltomaki & Salakoski, 2006).…”
Section: Agent-based Visual Programming and Tangible Computation For Chmentioning
confidence: 99%
“…Children find it difficult to understand the syntax and semantics of programming (Spohrer & Soloway, 1986;Perkins, 1988). They also find it challenging to effectively control the flow of a program using loops and conditionals (du Boulay, 1989). Researchers have also found that alleviating syntax problems helps students focus on the semantic ones (Hohmann, 1992;Soloway, 1993;Anderson, 1989;Mannila, Peltomaki & Salakoski, 2006).…”
Section: Agent-based Visual Programming and Tangible Computation For Chmentioning
confidence: 99%
“…In the glass box approach, students do have such an idea because the instruction includes a concrete but simplified computer model. This model makes it possible to emphasize a "notional machine" on both a general level, such as in teaching the relationship between the terminal and the computer and a specific level, such as in teaching assignment statements (DuBoulay, 1986). Mayer (1975) either gave students in an introductory BASIC course a concrete computer model or he did not.…”
Section: Concrete Computer Modelsmentioning
confidence: 99%
“…Learning and teaching computer programming is widely recognised as being a challenging undertaking within Higher Education (DuBoulay, 1989;Robins, Rountree, J. & Rountree, N. 2003;Winslow 1996) and does not appear to have become any easier over time.…”
Section: Introductionmentioning
confidence: 99%